2017
DOI: 10.1016/j.midw.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary randomised control trial of the effects of Dru yoga on psychological well-being in Northern Irish first time mothers

Abstract: the current study shows that Dru yoga is beneficial for the psychological well-being of first time mothers. Further research is needed using large scale replication studies with a longer follow up period and including multiparous women. This study extends the support for yoga with postpartum mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 62 publications
(57 reference statements)
1
53
0
2
Order By: Relevance
“…Physiologically, muscle resistance is known to decrease after childbirth along with hormonal changes that occur (19)(20). With the presence of physical exercise, especially yoga can improve muscle strength, stretching, and relaxation so that the quality of postpartum life is increased (21)(22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiologically, muscle resistance is known to decrease after childbirth along with hormonal changes that occur (19)(20). With the presence of physical exercise, especially yoga can improve muscle strength, stretching, and relaxation so that the quality of postpartum life is increased (21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise leads to increased levels of endorphins in the brain which acts as internal psychoactive agents to produce a sense of euphoria, a pleasant feeling associated with a positive self-image, a sense of vitality, control, and satisfaction, beta-endorphins produced endogenously from in the body during exercise (24). Yoga-based physical exercise as a holistic behavior has proven to be effective in improving psychological well-being, helping to build a recovery of physical strength after childbirth, and providing social support to postpartum mothers (21,25).…”
Section: Discussionmentioning
confidence: 99%
“…One study related to the PFMT exercise reported that kegel exercises carried out during the postpartum period can improve selfefficacy (Pourkhiz et al, 2017). Six studies reported that PFMT, PMR, postnatal exercises, pilates, and yoga have been shown to significantly improve the quality of life for postpartum women (F Ashrafinia et al, 2015;Gagnon et al, 2016;Gökşin & Ayaz-Alkaya, 2018;Mahishale et al, 2014;Sut & Kaplan, 2016;Timlin & Simpson, 2017). Four studies including aerobic exercise, pilates and yoga can improve the well-being of psychology in postpartum women (F Ashrafinia et al, 2015;Buttner et al, 2015;Timlin & Simpson, 2017;Yang & Chen, 2018).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Six studies reported that PFMT, PMR, postnatal exercises, pilates, and yoga have been shown to significantly improve the quality of life for postpartum women (F Ashrafinia et al, 2015;Gagnon et al, 2016;Gökşin & Ayaz-Alkaya, 2018;Mahishale et al, 2014;Sut & Kaplan, 2016;Timlin & Simpson, 2017). Four studies including aerobic exercise, pilates and yoga can improve the well-being of psychology in postpartum women (F Ashrafinia et al, 2015;Buttner et al, 2015;Timlin & Simpson, 2017;Yang & Chen, 2018). Other studies reporting on pilates and aerobics also reduced the fatigue and can improve the sleep quality of postpartum women (Farzaneh Ashrafinia et al, 2013;Yang & Chen, 2018).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Otro grupo poblacional sobre el cual los estudios realizados reflejan los beneficios de la práctica de yoga en los niveles de ES corresponde a las mujeres adultas y madres primerizas, donde se observa que tratamientos con una duración de cuatro a ocho semanas, entre 60 a 90 minutos y con una frecuencia de práctica de una vez por semana, junto con 20 minutos de práctica dos o más veces por semana, arrojan resultados, posterior a los periodos de intervención, relacionados con el incremento del bienestar psicosocial, disminuciones del estrés percibido y afectos negativos (Huang et al, 2013;Timlin et al, 2017).…”
Section: Estrés Psicológico Y Yogaunclassified